Analisis Hukum Terbitnya Sertifikat Ganda dan Mekanisme Penyelesaiannya - Sitti Annisa; Ahmad Rustan; Rudi Iskandar Ichlas; Wahyudi Umar (Jurnal Hukum Lex Generalis, 2024)
Control of the land plot must be proven through a valid certificate of ownership. In its development, it was found that there were duplicate certificates that overlapped each other. This study aims to provide an analysis related to the issuance of double certificates and the mechanism for their completion. This research is a normative juridical research with a legislative approach and a conceptual approach. The results of the study show that double certificates arise as a result of various factors, including administrative errors, lack of supervision, and the practice of abuse of authority in issuing certificates, thus creating legal uncertainty for land rights holders. The legal settlement requires a comprehensive approach, involving the improvement of the land administration system, and strict enforcement of any violations.